La semántica del ritmo en "la canción de amor de j . alfred prufrock " de t. s. ello (1997)
U n a l uch a in to l era b l e co n pa l a b ras y s i g n i f icados es la q u e h a n ve n i d o ) í b ra n d o l os e st ud i osos de l a obra de T . S. Ell o t a l o l arg o d e este s i g l o . C i e n tosde come ntari os, a rt ic ul osy li b r os, qu e va n des d e ) 0 e xce l e nt e h asta l o In ú til , d es d e e l an á li s i so bj et iv o ha sta l asu bj e ti v idadm ás extravaga n te ( Br oo k e r 2 36), h a n b usca d o p e n etrar e n e l sec ret o d e s u crea c i ó n p oé t ica; y n o to d os h a n h a ll ado e l ca m i n o m e di o e n tre l as a fi r m ac i o n es de f e y ese "sa b i o n o s a be r qu e ese l o pu esto d e l a i gn o r a n c i a" (M oo d y xív)